![image](https://tex.z-dn.net/?f=1%29+%5Cleft+%5C%7B+%7B%7B%28x-1%29%28x-6%29+%5Cgeq+0%7D+%5Catop+%7Bx-2%3C0%7D%7D+%5Cright.+%5C%5C%5C%5C+2%29+%5Cleft+%5C%7B+%7B%7B%28x-1%29%28x-6%29+%5Cleq+0+%7D+%5Catop+%7Bx-2%3E0%7D%7D+%5Crigaht.+%5C%5C%5C%5C+)
0}} \rigaht. \\\\ " alt="1) \left \{ {{(x-1)(x-6) \geq 0} \atop {x-2<0}} \right. \\\\ 2) \left \{ {{(x-1)(x-6) \leq 0 } \atop {x-2>0}} \rigaht. \\\\ " align="absmiddle" class="latex-formula">
Первое неравенство
Получаем решение
Второе неравенство
![image](https://tex.z-dn.net/?f=2%29+%5Cleft+%5C%7B+%7B%7B%28x-1%29%28x-6%29+%5Cleq+0+%7D+%5Catop+%7Bx%3E2%7D%7D+%5Cright.+%5C%5C%5C%5C+2%29%C2%A0%5Cleft+%5C%7B+%7B%7Bx+%5Cleq+1+%3B+%5C+%5C+x+%5Cgeq+6%7D+%5Catop+%7Bx%3E2%7D%7D+%5Cright.+%5C%5C%5C%5C+2%29%C2%A0%5Cleft+%5C%7B+%7B%7Bx+%5Cgeq+1%3B+x+%5Cleq+6%7D+%5Catop+%7Bx%3C2%7D%7D+%5Cright.+)
2}} \right. \\\\ 2) \left \{ {{x \leq 1 ; \ \ x \geq 6} \atop {x>2}} \right. \\\\ 2) \left \{ {{x \geq 1; x \leq 6} \atop {x<2}} \right. " alt="2) \left \{ {{(x-1)(x-6) \leq 0 } \atop {x>2}} \right. \\\\ 2) \left \{ {{x \leq 1 ; \ \ x \geq 6} \atop {x>2}} \right. \\\\ 2) \left \{ {{x \geq 1; x \leq 6} \atop {x<2}} \right. " align="absmiddle" class="latex-formula">
Получаем решение
Объединяя